MODEL HYBRID FLOW SHOP 3 STAGE TO MINIMIZE MAKESPAN - Damur Rochman, Didit (International Journal of Psychosocial Rehabilitation, 2020)
Hybrid flow shop production system is currently widely applied in manufacturing companies, one of the companies implementing it is PT XYZ which is engaged in the production of fishing net manufacturing. The HFS system is a production system consisting of several stages with identical or non-identical engine configurations. Based on observations that have been made problems arise when a new job comes while a stage is still producing a previous job. This resulted in the work having to wait until the previous work was completed. These conditions make the time of completion of a job (makespan) become hampered. This study aims to develop a hybrid flow shop production system model with the aim to reduce the makespan. Based on the results of data processing, it was found that by using the HFS model the time needed to produce 10 jobs was 295.25 with a computation time of 3.47 minutes using LINGO software.